Training to Communicate Effectively : Documentary Comparative Analysis of the Portuguese Training Offer - Sílvia Queirós; Rute Meneses; Germano Couto (Instituto Politécnico de Viseu, 2023)
Introduction: Health professionals' specific and adequate training in clinical communication is of utmost importance for adequate communication with the patient. Objective: To identify and analyze postgraduate and professional training courses in clinical communication or communication skills, for physiotherapists, in Portugal through a documental comparative analysis. Material and Methods: Online research was conducted in training organizations for physiotherapists and/or health professionals and online pages of different universities and polytechnic institutes with postgraduate and professional training for physiotherapists. Results: The search allowed the identification of eight training courses in clinical communication aimed at physiotherapists.The courses were analyzed and compared in training, recipients, hours, objectives, syllabus, teaching methodology, and assessment type. All courses are theoretical-practical, with a workload ranging from eight to 100 hours, six face-to-face courses, and two online. All programs were addressed to health professionals from different areas, and none specifically addressed physiotherapists. There was considerable homogeneity regarding syllabus content and teaching methodologies. Conclusions: The study allowed identifying and characterizing the training courses in clinical communication available in Portugal, aimed at physiotherapists, which improves the physiotherapist-patient communication relationship. The teaching methodology was expository, theoretical, and practical, with the visualization of clinical vignettes, role-play activities, and interviews with simulated patients.